2018
DOI: 10.29312/remexca.v4i8.1130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la composta de bagazo de agave como componente de sustratos para producir plántulas de agave azul tequilero

Abstract: El agave azul es la materia prima para la producción de tequila a través de un proceso de destilación que genera alrededor de 400 mil toneladas anuales de bagazo, el cual, parcialmente, se transforma en composta. Las plantas de agave micropropagadas requieren un periodo de adaptación de alrededor de nueve meses en vivero o invernadero tipo casa sombra, para lo cual se cultivan en contenedor con un sustrato comercial. Para esta etapa, no existen aún parámetros morfológicos que sirvan como r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
6
0
4
Order By: Relevance
“…As a result, annual estimates of bagasse production have regularly exceeded 300,000 t (CRT, 2016). Although the use of tequila by-products has been explored by a growing number of researchers, it is known that clandestine and landfill disposal still occurs (Crespo González et al, 2013).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, annual estimates of bagasse production have regularly exceeded 300,000 t (CRT, 2016). Although the use of tequila by-products has been explored by a growing number of researchers, it is known that clandestine and landfill disposal still occurs (Crespo González et al, 2013).…”
Section: Figurementioning
confidence: 99%
“…They reported that the strength of pulps from the agave fibre was poorer than wood and other agro-based pulps. Iñiguez-Covarrubias et al, (2001) used ATF to substitute corn stubble in livestock feed; whereas Crespo González et al, (2013) studied composting the fibres. ATF has also been used to fabricate carrier bags and containers (Hernandez, 2017).…”
Section: Figurementioning
confidence: 99%
“…Por otra parte, Crespo- González et al (2013) trabajaron con plantas micropropagadas in vitro de Agave tequilana Weber var. azul con una altura de 15-22 cm y 16 meses de edad, en donde evaluaron la respuesta de las plantas a los tratamientos establecidos a base de formulaciones de los sustratos orgánicos (polvo de coco (PC), turba (T) y composta de bagazo de agave (C), mezclados en una relación de volumen (v/v), considerándose los siguientes: 1) testigo: 80% PC + 10% T + 10% C; 2) 100% PC; 3) 100% T; 4) 70% PC + 30% C; 5) 50% PC + 50% C; 6) 30% PC + 70% C; y 7) 100% C. Además, las plantas de todos los tratamientos durante nueve meses recibieron entre 7 y 14 fertirriegos por mes con quelatos de hierro y manganeso, sulfato de magnesio, nitrato de calcio, y fórmulas N-P-K 18-18-18 (período septiembre-diciembre) y 15-30-15 (período enero-mayo).…”
Section: Características De Plantas Micropropagadas De Agave Americana Var Oaxacensis Al Finalizar Su Aclimatizaciónunclassified
“…En algunos estudios sobre la aclimatización de plantas de agave micropropagadas se ha demostrado en A. tequilana (Crespo- González et al, 2013) y A. potatorum Zucc. (Enríquez-del Valle et al, 2016 que logran mayor crecimiento cuando reciben abastecimiento adecuado de nutrimentos, ya sea mediante soluciones nutritivas o incorporando fertilizantes minerales a los sustratos, comparadas con plantas que no reciben fertilización.…”
Section: Introductionunclassified
“…Zavala & Nava, 2017). Therefore, strategies have been proposed to minimize the impact of this waste and, at the same time, valorize it, for example: production of biopolymers and carbohydrases, phenolic compounds, biohydrogen, biogas and bioethanol; when used as a substrate under fermentative processes: compost for the production of substrates to produce agave seedlings, production of activated carbon (González-García et al, 2005;Crespo-González et al, 2013;2018;Pérez et al, 2018;Estrada-Maya & Weber, 2022), raw material for brick manufacturing and mattress filling, as well as fuel in boilers and forage for poultry and livestock (Iñiguez et al, 2011) and in mezcal factories themselves (Chávez & Hinojosa, 2010). In the biotechnology industry, it has been used to obtain pulp for the production of paper, cardboard, cork and as a substrate for mushroom cultivation (Chairez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%